Characterization of Ibero-American universities by SDG in Times Higher Education Impact Rankings 2020 - et al., Marisabel Luna Cardozo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An alternative to evaluate and compare the social and economic impact of universities in pursuit of Sustainable Development Goals (SDGs) of United Nations (UN) is to measure metrics of Times Higher Education Impact Rankings. In 2020, it includes 128 Ibero-American universities out of 768 or 806 total universities, that figure will need to be clarified. This paper aims to analyze and compare, through a descriptive analysis, Ibero-American universities in Times Higher Education Impact Rankings 2020 in order to contrast performance of the institutions by SDG. 16.67% of Ibero-American universities classify in overall ranking and in SDG 17. 9.81% classifies in SDG 8. 9.68% in SDG 3. 7.69% in SDG 4.